Grounding the idea of renewal in Islamic thought, and collective ihya': a study from the perspectives of the philosophy of religion and fiqh - Yildirim, Husamettin; Gulengul, Esra (Springernature, 2025)
The idea of renewal in Islam as a comprehensive system is based on the basic premise that it must provide appropriate solutions to all conceivable problems related to religious matters at both the individual and societal levels in every era. A brief look upon the problems present in the Muslim world today clearly reveals the significance of renewal. All aspects touching individual and societal life require evaluation, reconsideration, and, moreover, revitalisation in terms of their relationship with religion. This necessity constitutes grounding the idea of renewal at a certain stage. Academic studies on renewal in Islam have predominantly adopted a historical perspective and focused on movements and currents, mostly referred to as tajdid. However, we argue that the intellectual and rational dimensions of the idea of renewal have been overlooked. At this point, numerous questions arise, such as: Is there a need for renewal in Islam? Is renewal possible? Is renewal legitimate? What are the scope and boundaries of renewal? Can institutional or continuous renewal be discussed? Can a new renewalist approach be developed today? This study, which focuses on these questions, is interdisciplinary research within the philosophy of religion and fiqh (Islamic jurisprudence) framework. The study employs methods of conceptual analysis, historical enquiry, philosophical argumentation, and critique. It aims to establish a holistic framework for rationally grounding the idea of renewal in Islam, specifically through the concept of ihyah. Additionally, it proposes the approach of collective ihya' as an alternative in the context of contributing to the reconstruction of Islamic civilisation. Collective ihya' is a humble and intellectual approach that aims to realise the transition from individual awareness to social awareness and then to universal awareness through tolerance and persuasion.